Effectiveness of Human Resources Managements in Riyadh’s Private Universities - Al-Askar, Sara Fahad; Al-Twaijri, Najla Mohammad; Al-Twaijri, Fatimah Abdulaziz (Journal of Educational and Psychological Sciences, 2021)
The Study aims at discovering how effective the Human Resources Managements (HRMs) in some of Riyadh’s Private Universities are. To achieve this main objective, the researchers used the descriptive approach and applied a scale that consists of 70 questions covering 9 issues, and it was applied to all managers of human resources departments and their employees, the total number of participants is 36 which represents the total of the HRMs’ heads and employees of the privet universities: (Prince Sultan University, Dar Al Uloom University, AlMaarefah University, and Arab Open University) in Riyadh. The study found several significant results. One of them is that the participants agreed to a certain extent that HRMs are effective in their universities. The results also show that the HRMs are highly effective in devices and software used in HRMs’ issue as its score was Average, followed by policies, strategies and objectives of the HRMs’ issue as its score was Average as well. The remaining issues came, according to their scores, in the following sequence: HRMs’ planning’s issue, headhunting, recruiting, and supporting HRs’ issue, legislations of the HRMs’ issue, performance evaluation issue, work design and analysis’s issue, HRMs’ training’s issue, and finally salaries and both material and nonmaterial incentives’ issue. Based on the findings and conclusions, the researchers’ recommendations include encouraging HRMs in Private Universities in Riyadh to provide flexible and effective incentives programs to encourage their employees and increase their affiliation to the organization and designing clear-cut performance evaluation criteria and measurements.